Den første olje - Jenssen, Hugo Lauritz (Ambra : Sandefjordmuseene årbok, 1999)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

The Southern Ocean seabed: arena for conflicting regimes? - Vidas, Davor (Order for the oceans at the turn of the century, 1999)
Keywords: Sørishavet; jus

Polare jubileer i 1997 og 1998 - Barr, Susan (Polarboken, 1998)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Moorings from the Filchner Trough and the Ronne Ice Shelf front: preliminary results - Woodgate, Rebecca A; Schröder, Michael; Østerhus, Svein (Filchner-Ronne Ice Shelf Programme. Report, 1998)
Keywords: Sørishavet; oseanografi

Indentation testing on ice from the Filchner Ronne Ice Shelf area, Antarctica: preliminary results - Gerland, Sebastian (Filchner-Ronne Ice Shelf Programme. Report, 1997)
Keywords: Antarktis; Sørishavet; glasiologi; havis

Characteristics of Weddell Sea Shelf sediments obtained by diamond core drilling, Antarctica - Strand, Kari; Kristoffersen, Yngve (FINNARP -95/96: Weddel Sea Joint Nordic Expedition, 1997)
Keywords: Sørishavet; geokjemi; sedimenter

Marine geology of the continental shelf off the Riiser-Larsen Ice Shelf, eastern Weddell Sea, Antarctica - Winterhalter, Boris; Kotilainen, Aarno; Cato, Ingemar; Kjellin, Bernt; Jakobsson, Martin; Kristoffersen, Yngve (FINNARP -95/96: Weddell Sea Joint Nordic Expedition, 1997)
Keywords: Sørishavet; geologi; maringeologi

Den nordiske Antarktisekspedisjonen 1995/1996: Rapport om grunn kjerneboring på kontinentalsokkelen i Weddelhavet, Antarktis - Kristoffersen, Yngve (Inst. for den faste jords fysikk, UiB, 1996)
Keywords: Sørishavet; ekspedisjoner; geologi

Formation and circulation of Ice Shelf Water in the Weddell and Ross seas - Nøst, Ole Anders (University of Bergen, 1995)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Subantarctic island research: discussion and recommendations - Sømme, Lauritz (Progress in conservation of the Subantarctic islands: proceedings of the SCAR/IUCN Workshop on Protection, Research and Management of Subantarctic Islands, Paimpont, France, 27-29 April 1992, 1995)
Keywords: Sørishavet; forskning; forvaltning; natur

Water mass distribution and tides along the Filchner-Ronne ice shelf: preleminary [sic] results from the Norwegian Antarctic Expedition 1992/93 - Gammelsrød, Tor (Filchner-Ronne Ice Shelf Programme. Report, 1994)
Keywords: Sørishavet; oseanografi

Distribution of Water Masses on the Continental Shelf in the Southern Weddell Sea - Gammelsrød, Tor; Foldvik, Arne; Nøst, Ole Anders; Foldvik, Ø.; Anderson, Leif G.; Fogelqvist, Elisabet; Olsson, K. Anders; Tanhua, Toste; Jones, Elizabeth Peter; Østerhus, Svein (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
Water properties on the continental shelf in the southern Weddell Sea observed during NARP 92/93 are presented. The station distribution includes a section close to the floating ice shelf from the Filchner Depression to the Antarctic Peninsula. Temperature, salinity, oxygen, silicate, CFC-ll and CFC-12 distributions are shown. Melting under the ice shelves, circulation systems, residence times, sediment/water interactions and bottom water formation are discussed. Ice Shelf Water (ISW), which is formed by cooling and melting below the floating ice shelf, seems to be about 10 years older than its parent water mass, which indicates the residence time below the ice shelf. The average melting rate below the Filchner Ronne ice shelf, based on the volume flux of ISW in the Filchner Depression is estimated to be 0.1 m/year. Compared with earlier observations considerable changes were found in the water characteristics and distribution: The temperature of the Weddell Deep Water has increased 0.7°C since 1977. Western Shelf Water, usually dominating the bottom layers in the Filchner Depression and on the Berkner Shelf, was found only in the Ronne Depression.
Keywords: NARP 1992/93; Sørishavet; Weddellhavet; geofysikk; oseanografi

Hvalfangstens økonomiske betydning for Vestfold i mellomkrigstiden - Olsen, Per Erik (P.E. Olsen, 1994)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstindustri; hvalindustri

The legitimacy of the Convention on the Conservation of Antarctic Marine Living Resources - Davis, Bruce W; Herr, Richard A (Fridtjof Nansens institutt, 1993)
Keywords: Sørishavet; jus; miljøvern; politikk

The Antarctic Treaty system and the law of the sea. Review of Christopher C. Joyner: Antarctica and the law of the sea - Vidas, Davor (International Challenges, 1993)
Keywords: Sørishavet; jus; litteratur

Bunnvannsstrømmer på kontinentalskråningen i Weddellhavet - Nordlund, Nina (Universitetet i Bergen, 1992)
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; havstrømmer; oseanografi

En modell for sirkulasjonen under isshelfene i Weddelhavet og Rosshavet - Nøst, Ole Anders (O. A. Nøst, 1992)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Gigantisk isfjell i Sør-Atlanteren - Orheim, Olav (Polarboken, 1992)
Keywords: Sørishavet; glasiologi; isfjell

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

Conference report: preservation or exploitation - Stokke, Olav Schram (Marine Policy, 1991)
Keywords: Sørishavet; forvaltning; jus; politikk

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

The practical implications of the eco-system approach in CCAMLR - Beddington, John R; Basson, M; Gulland, J A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Has CCAMLR worked? management policies and ecological needs - Heap, John A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Glaciologic and oceanographic studies on Fimbulisen during NARE 1989/90 - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1990)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; glasiologi; isbrem; oseanografi

The implementation of CCAMLR: is the decision-making machinery conductive to good management? - Orrego Vicuña, Francisco (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; miljøvern; politikk

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk